2016
DOI: 10.1016/j.solmat.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature deposition of homogeneous, highly transparent and conductive Al-doped ZnO films by reactive high power impulse magnetron sputtering

Abstract: Room temperature deposition of homogeneous, highly transparent and conductive Aldoped ZnO films by reactive high power impulse magnetron sputtering, Solar Energy Materials and Solar Cells, 2016. 157, pp.742-749. http://dx. AbstractAluminium doped zinc oxide (AZO) films have been deposited using reactive high power impulse magnetron sputtering (HiPIMS) and reactive direct current (DC) magnetron sputtering from an alloyed target without thermal assistance. These films have been compared in terms of their optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 34 publications
(37 reference statements)
5
43
0
Order By: Relevance
“…At the same time, it allows control of the flow of ions to the substrate, which could lead to improved crystallinity. HiPIMS allow to the producing of highly transparent and conductive AZO films on large surfaces without thermal assistance . The deposition rates are high, which is advantageous for industrial applications.…”
Section: Magnetron Sputtering Of Azomentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it allows control of the flow of ions to the substrate, which could lead to improved crystallinity. HiPIMS allow to the producing of highly transparent and conductive AZO films on large surfaces without thermal assistance . The deposition rates are high, which is advantageous for industrial applications.…”
Section: Magnetron Sputtering Of Azomentioning
confidence: 99%
“…Recent results are consistent with these claims. It was reported that the electrical properties of AZO films deposited by HiPIMS are more homogeneous compared with conventional dc or RF magnetron sputtering. AZO films prepared by HiPIMS at higher voltage do not exhibit the spatial distribution of the resistivity.…”
Section: Magnetron Sputtering Of Azomentioning
confidence: 99%
“…One is the intrinsic stress induced by the impurities and defects in the crystal, and the other is the extrinsic stress introduced by the lattice mismatch and the thermal expansion coefficient mismatch between the film and the substrate. The later component is negligible compared to the stress measured in the former [27,28], when the films were deposited at lower substrate temperature.…”
Section: Structural Investigationsmentioning
confidence: 82%
“…The increased stress in the films was due to the nonstoichiometry of the Mo atoms in the films, that is, a sufficient at.% of Mo in the target was not present in the films. However, the decreased stress in the films doped with 2 at.% Mo was due to the growth of additional crystallographic orientations and oxygen substoichiometry [29,30],which inhibit the growth of the (002) orientation. By contrast, the stress in the films deposited at higher substrate temperatures increased with the at.% of Mo, even when the stoichiometric ratio of Mo in ZnO was maintained in the films.…”
Section: Structural Investigationsmentioning
confidence: 98%
“…and can be more uniformly coated as well [21][22][23]. Recently, reactive HiPIMS in various gas mixtures has been used for the deposition of oxides, nitrides, and other materials [24][25][26][27][28][29][30][31].In this paper, we will present the first study of plasma parameters in the reactive HiPIMS in Ar + H 2 S gas mixture whose results could be further used for the optimization of deposition of iron sulfide thin films or other types of sulfides.…”
mentioning
confidence: 99%